Health claim effects on consumer acceptability, emotional responses, and purchase intent of protein bars - Mishika Thakur; Chetan Sharma; Annu Mehta; Damir D. Torrico (Journal of Agriculture and Food Research, 2022)
Consumers are seeking product's claims to make their daily food purchase decisions more informed. In this context, health claims can communicate to consumers about nutrient-specific health benefits. The objective of this research was to study the effect of health claims, in textual form, on consumers' acceptability, emotional responses, and purchase decisions regarding protein bars. For this study, four protein bars were selected by a focus group (N = 6) based on acceptability. A total of N = 80 participants evaluated the pre-selected protein bars in two different tasting sessions [(1) Blind, where no information was provided, and (2) Informed, where health-related information of protein bars was provided]. Participants rated their liking for different sensory attributes (appearance, aroma, taste, texture, sweetness, bitterness, and aftertaste) and overall liking using a 9-point hedonic scale. Check-all-that-apply (CATA) was used to study emotions and 22 terms related to sensory attributes of the protein bar. There was a non-significant increase in the purchase intent for three out of four samples in session 2 but it was found to be high for the sample associated with positive emotions. Overall, this study showed that taste overpowered the health claims (expressed in textual form) on the acceptability. There were, however, slight effects of the health claims on the elicited emotions of consumers towards the protein bars.